A Multi-scale U-Net for Semantic Segmentation of Histological Images from Radical Prostatectomies - Li, Jiayun; Sarma, Karthik V; Chung Ho, King; Gertych, Arkadiusz; Knudsen, Beatrice S; Arnold, Corey W (AMIA ... Annual Symposium proceedings, 2017)
Gleason grading of histological images is important in risk assessment and treatment planning for prostate cancer patients. Much research has been done in classifying small homogeneous cancer regions within histological images. However, semi-supervised methods published to date depend on pre-selected regions and cannot be easily extended to an image of heterogeneous tissue composition. In this paper, we propose a multi-scale U-Net model to classify images at the pixel-level using 224 histological image tiles from radical prostatectomies of 20 patients. Our model was evaluated by a patient-based 10-fold cross validation, and achieved a mean Jaccard index of 65.8% across 4 classes (stroma, Gleason 3, Gleason 4 and benign glands), and 75.5% for 3 classes (stroma, benign glands, prostate cancer), outperforming other methods.